Coffee’s influence on social interaction, energy and physical performance - Zainudin, Intan Julia; Mohammad, Tajulurrus; Amirruddin, Muhamad Amirul Badlishah; Edros, Siti Aishah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
Coffee consumption is widespread among university students, often is associated with perceived benefits such as improved concentration, higher energy, and enhanced social interaction. However, excessive intake may contribute to health risks including sleep disturbances and anxiety. This study examined coffee consumption patterns and perceptions among students at Universiti Teknologi MARA (UiTM) Dungun, Terengganu. A total of 380 responses were collected through structured questionnaires and analysed using SPSS Version 27. Descriptive analysis revealed that 37.4% of students consumed coffee one to two times daily, with many associating it with improved alertness and motivation. However, regression analysis showed that only physical performance enhancement was significantly related to coffee consumption, whereas social interaction and energy levels were not. These findings underscore the inconsistent nature of caffeine’s perceived effects and the need for greater awareness of responsible intake. Future research should consider larger and more diverse samples to strengthen health education strategies.